Integrating The Indexation Method Into Uzbekistan’s Cadastral Valuation System: Mengintegrasikan Metode Indeksasi ke dalam Sistem Penilaian Kadaster Uzbekistan - Ulugbek Tulakov (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In modern tax systems, aligning cadastral values with real market conditions is essential for fair and accurate taxation. Specific Background: Uzbekistan’s current static cadastral valuation system lacks mechanisms to promptly reflect changes in market prices, leading to inefficiencies and tax inequities. Knowledge Gap: Despite modernization efforts, there is no established method for periodically updating cadastral values in response to economic fluctuations. Aims: This study aims to assess the feasibility of integrating indexation into Uzbekistan’s cadastral valuation system and propose a suitable methodology. Results: The research shows that indexation—used globally in countries like Belgium, Spain, and Italy—enhances valuation accuracy, ensures fairer tax burdens, and stabilizes government revenues. Novelty: The study offers a tailored methodology based on international best practices and adapted to Uzbekistan’s specific institutional and data contexts, emphasizing automated integration and public transparency. Implications: Implementing indexation will promote equity in property taxation, reduce administrative burdens, and support the development of a stable, transparent, and adaptive cadastral system aligned with market dynamics.Highlight : Ensures Tax Accuracy – Indexation aligns property values with market conditions, improving fairness and equity in real estate taxation. Supports Fiscal Stability – Regular value updates through indexation help maintain a predictable and stable tax base. Adaptable Integration – The proposed model allows integration with existing digital systems like CAMA for efficient implementation. Keywords : Cadastral Value, Indexation Method, Real Estate Tax, Tax Accuracy, Market Price Index.